URGENCY PUBLIC DATA PROTECTION BASED ON DATA LEAKAGE CASES AT THE INDONESIAN CHILD PROTECTION COMMISION - Raineven Sailano Violand Charnade (Constitutionale, 2022)
Privacy is the essential thing regulated in Human Rights. As a country that recognizes human rights, Indonesia is a state that adheres to the principles of human rights and also recognizes that privacy is a human right that the state must protect. However, no law addresses the issue of public data protection in Indonesia comprehensively. On Monday, October 18, 2021, data leaks on the identity of the complainant and underage victim, case summary, and mediation results were found. It has at least two significant impacts, firstly it can impact the inhibition of KPAI's performance due to public trust, and secondly, it will have a worse impact on victims and whistleblowers, both physically and mentally, because this can trigger predatory movement. The research method used is normative legal research based on secondary data library research which is descriptive, evaluative, and prescriptive. Several approaches are used, namely the legal approach, conceptual, to answer the first question, the point of contact between individual and state interest, and a comparative approach to answer the second problem regarding the dynamics of personal data protection arrangements in the problem of data leakage experienced by KPAI. Therefore, Indonesia needs to immediately legitimate the Draft Law on Public Data Protection (RUU PDP) so that the urgency of the legalization of public data protection can be immediately resolved.